PENERAPAN PELAYANAN PRIMA BERBASIS INOVASI KLAMPID NEW GENERATION (KNG): (Studi di Kantor Kelurahan Pakal Kecamatan Pakal Kota Surabaya) - Julian Irvanda Wijaya Putra; Radjikan Radjikan; Indah Murti (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
In order to facilitate the process of population needs related to population administration, the Department of Population and Civil Registration of course continues to innovate. One of the innovations to carry out their duties in serving government affairs and public services, the Surabaya City Population and Civil Registry Office created the Klampid New Generation (KNG) innovation. Through sub-districts and sub-districts, this study aims to evaluate the implementation of KNG-based excellent service at the Pakal Village Office. This study uses a qualitative descriptive approach by collecting data through interviews, observation, and documentation. The focus of research on the implementation of KNG-based excellent service at the Pakal Kelurahan Office in Surabaya City is based on the Barata theory indicators of Capability, Attitude, Appearance, Attention, Action, and Responsibility. The results of this research regarding the new generation of Klampid innovation services are (1) The community is satisfied with the service in terms of attitude, attention, action and responsibility of the Kelurahan service staff in providing population administration services, namely friendly, good and clear in providing information. (2) Lack of capacity due to limited human resources in the Kelurahan results in delays in service delivery. (3) People are sometimes confused about where to go when they are in the kelurahan due to office renovations and some services being diverted to the local RW Hall.